Transoral endoscopic vestibular approach Sistrunk procedure: First reported case series. Issue 1 (25th October 2021) - Banuchi, Victoria E.; Long, Sallie M.; Sachs, Bracha Y.; Kostas, Julianna C.; Ali, Khalid M.; Russell, Jonathon O.
Abstract: Background: Standard of care for management of thyroglossal duct cysts (TGDCs) is a Sistrunk procedure performed through a transcervical incision. We describe the first series of Sistrunk procedures performed through a transoral endoscopic vestibular approach, eliminating a visible external scar. Methods: The transoral endoscopic vestibular approach to the Sistrunk (TEVAS) was performed in patients with TGDCs meeting inclusion criteria who desired a scarless approach. Results: Six patients (five females and one male) underwent TEVAS, with a mean age of 38 years (range 16–56 years) and a mean TGDC size of 1.8 cm (range 1.1–2.4 cm). Mean operative time was approximately 5 h (range 2–8 h). There were no surgical complications or recurrences. Conclusions: For appropriately selected patients, the TEVAS is an alternative to open neck surgery that provides improved cosmesis while maintaining successful resection outcomes. More data on outcomes including complications and recurrences are needed as additional case information is collected.